Knowledge, perceptions, and practices around zoonotic diseases among actors in the livestock trade in the Lake Victoria crescent ecosystem in East Africa - Majiwa, Hamilton; Bukachi, Salome A.; Omia, Dalmas; Fèvre, Eric M. (Frontiers in Public Health, 2024)
Zoonotic diseases like anthrax, rabies, brucellosis, and Rift Valley fever pose a direct threat to health and undercut livelihoods in the communities in which they occur. A combination of anthropogenic and animal activities like migration and interaction with wildlife and their respective parasites and vectors drives the emergence and re-emergence of zoonotic diseases.Consequently, One Health interdisciplinary approaches that incorporate social scientists can provide key insights into complex local perceptions. The approach calls for collaboration between the human and animal health sectors, including the sharing of disease surveillance data necessary to alleviate disease impacts. Livestock traders interact closely with livestock, which puts them atThe actors involved in the livestock trade are critical in the prevention and elimination of zoonotic diseases; hence they need to be involved when developing intervention programs and policies for the animal health extension services. Training them as a continuum of animal health workers blends lay and professional knowledge, which alongside their intense contact with large numbers of animals becomes a critical disease surveillance tool. Increasing awareness of zoonoses by using multi-disciplinary teams with social scientists is needed urgently so that practices like skinning of dead animals before disposing of them and consumption of dead carcasses can be minimized.